Pre-implementation knowledge tool development for health services providers: A qualitative study of Canadian social workers. (May 2014) - Dykeman, Sarah; Williams, Allison; Crooks, Valorie
Recent research has shown that social workers are particularly well placed to disseminate information about health-related social programs such as Canada's Compassionate Care Benefit (CCB). Low uptake of the CCB may be due, in part, to a lack of knowledge. In response to this, we report on the development of CCB knowledge tools aimed specifically at social workers. Social worker-specific tools about the CCB were developed through a multi-step process. Using a computer-based qualitative messaging survey ( n = 16), social workers chose what they determined to be the most important messages needed to gain knowledge about the CCB. Using these chosen messages, draft tools were created and then refined for content and aesthetics using a focus group ( n = 8) and information from key informant interviews ( n = 3). Further research is needed to evaluate tool implementation effectiveness and use in practice. This study contributes to the understanding of knowledge translation strategies specific to social workers, and particularly those working in end-of-life settings.